Joint public procurement in European Union Law - Radomír Jakab (Prawo Budżetowe Państwa i Samorządu)
One of the areas related to the drawing and use of the budget funds of particular member states, as well as European Union (EU) funds, is public procurement. EU law allows particular contracting authorities or sector procurers to cooperate within public procurement and procure commodities jointly, i.e. to implement the joint public procurement procedure. This procedure is undoubtedly advantageous, especially in terms of cost savings; however, it also has a few drawbacks, particularly the ambiguity of legal regulations regarding the application of particular institutes in such joint public procurement. This paper aims to examine the theoretical and legal basis of joint public procurement, define the individual forms of joint public procurement under consideration, highlight the existing application-related problems in the implementation of this procedure and indicate possible legal solutions to the identified legal problems based on the interpretation of the relevant provisions of legal regulations.